1997
DOI: 10.1148/radiology.204.2.9240518
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity central venous obstruction in hemodialysis patients: treatment with Wallstents.

Abstract: After suboptimal angioplasty, treatment of subclavian and brachiocephalic vein stenoses with a Wallstent can provide continued use of a hemodialysis access. Close clinical surveillance and multiple reinterventions are necessary to maintain Wallstent patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(79 citation statements)
references
References 0 publications
6
71
1
1
Order By: Relevance
“…1,[15][16][17][18][19][20][23][24][25][26][27][28] Additionally, also in common with other authors, 20,21 we did not observe superior patency in angioplasties with stents. Notwithstanding, our results differ with …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…1,[15][16][17][18][19][20][23][24][25][26][27][28] Additionally, also in common with other authors, 20,21 we did not observe superior patency in angioplasties with stents. Notwithstanding, our results differ with …”
Section: Discussionsupporting
confidence: 84%
“…This could reduce the intimal hyperplasia response, reducing restenosis rates after angioplasty. 27 Kundu 32 published a study in which shorten or fracture, and their use may impede future endovascular procedures or surgery. Furthermore, it is already evident that all stents can provoke intimal hyperplasia, leading to recurrent stenosis and multiple interventions to maintain patency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore we have to utilize all the interventional radiological methods for SVC outflow site repair before the decision on its unfitness. Surgical repairs in SVC central veins region are usually not possible due to extreme operating and complication rate risk [16][17][18][19] . Thorough preoperative vessel evaluation and the stable hemodynamic and coagulative condition of the patient are the basic prerequisites to prevent fistula failure 7,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Veselyet aJ. [12] evaluatedthe effectivenessof Wallstentsin treatingsubclavianandbrachio cephalic vein obstruction after unsuccessful angioplasty in hemodialysispatients.Thesere searchers found that Wallstents could be effec tive in salvaging hemodialysis access but that reintervention wasoftennecessary to preserve stent patency. Our experience indicates that re intervention may often be necessary to pre servepatency in Wallstents placed in the NC aswell.…”
Section: Ajr:171 July 1998mentioning
confidence: 99%